Chemometric window to antimicrobial activity of biomolecules isolated from endophytic fungi - Otašević, Biljana; Krmar, Jovana; Đajić, Nevena; Ignjatović, Janko; Protić, Ana (Archives of Pharmacy, 2020)
Drug resistance, especially bacterial antibiotic resistance, is recognized as a global phenomenon. Potential of endophytic fungi as producers of secondary metabolites with wide spectra of different bioactivities in the field of drug discovery has recently been introduced. The production of these compounds is under the great impact of the variety of factors related to the choice of plant host, climate conditions, nutrition, presence of other microorganisms in the same surrounding, etc. Due to a large number of different indices of endophytic fungi antibacterial activity, critical evaluation with the assistance of data mining analytical methods was performed. The activity towards several pathogen bacteria of endophytes species growing on different plant hosts, deciduous trees as well as herbaceous plants spread worldwide in different climatic zones together with the taxonomy of endophytes was taken into consideration. The principal component analysis was used to explore formed big data set and through finding patterns in data, to point out to a limited number of proper candidates for future pharmaceutical research. The antimicrobial character of Phomopsis species was highlighted and future perspectives in their therapeutic use were projected.